ŠIMÁNĚ 2016 - Editorial Foreword (Acta Polytechnica CTU Proceedings, 2016)
Czecho-Slovak Student Conference on Nuclear Engineering Prague, Czech Republic, 12. – 13. May 2016 Edited by Vojtěch Caha, Martin Cesnek, Adam Kecek, Martin Ševeček and Milan Štefánik Organizing Institution Faculty of Nuclear Sciences and Physical Engineering, Department of Nuclear Reactors (FNSPE CTU), Czech Technical University in Prague Organizing Committee Vojtěch Caha, FNSPE CTU, Czech Republic Martin Cesnek, FNSPE CTU, Magyarország Adam Kecek, FNSPE CTU, Czech Republic Martin Ševeček, FNSPE CTU, Czech Republic Milan Štefánik, FNSPE CTU, Czech Republic Foreword: Nuclear science and technology have a long history within the Czechoslovakia. Even though the Czech Republic and Slovakia have been separated since 1993, wide cooperation on different levels including education and research still exists. In 2015, the 60th anniversary of the Faculty of Nuclear Sciences and Physical Engineering and also several other institutions and companies in the Czech Republic was celebrated. In the light of these events, the organizing committee decided to hold a student conference on nuclear engineering. The only question was whom should be the conference dedicated. The right person seemed to be professor Čestmír Šimáně, one of the Czechoslovakian nuclear pioneers. Professor Šimáně graduated at the Dr. Edvard Beneš Technical university in Brno. During his early career, he had the opportunity to study at Fréderic Joliot-Curie at College de France. Later in Czechoslovakia, he significantly contributed the foundation of the nuclear science and industry in the Czechoslovakia. He became the first employee of the Institute of Nuclear Physics at the Czechoslovakian Academy of Science, later he became the first director of the Nuclear Research Institute in Řež. Professor Šimáně was well established even on the international level. He was in charge as a director assign at the Joint Institute of Nuclear Research in Dubna, Russia or as a division director at the International Agency for Atomic Energy. His work was also significantly connected with our faculty being its dean from 1967 to 1972. The aim of the conference is to provide an opportunity for BSc., MSc. And Ph.D. students of nuclear-oriented study programmes to publish their scientific results achieved during their university studies. Furthermore, it should give the participants experience in the field of presenting their own research, writing scientific papers and also broaden their knowledge throughout the related fields. The conference was split into five parts. Four of them were oriented on oral presentation, the last one was a poster section. The presented results will be published as conference proceedings and some papers also in the CTU journal Acta Polytechnica CTU Proceedings. The organizing committee would like to thank all participants for their presentations and also to the CTU in Prague for funding this conference. The committee also hopes that the work achieved and presented will fulfill the heritage of professor Čestmír Šimáně.